Data Processing Payment of Educational Guidance Contributions at Al Ihsan Pamarican High School, Ciamis Regency - Lady Gardi (Journal of Intelligent Decision Support System (IDSS), 2021)
The use of computer technology, especially in terms of data processing, is currently very necessary, both for the benefit of individuals and for an agency, including the payment system for the Educational Development Contribution (SPP) at SMK Al-Ihsan Pamarican. The tuition payment process at Al-Ihsan Pamarican Vocational School requires a recording, processing, storage and report on students who make payments. The problems mentioned above, the authors create a payment data processing system that aims to build a payment data processing of educational assistance donations that is easy to use, and can be relied on and ensures the availability of data. The result of this final project is in the form of a payment system that can be implemented at the Al-Ihsan Pamarican Vocational School, or other educational institutions. which can eventually be used for the storage, processing, and reporting of computerized payment data. With the implementation of a computerized system or application program, in providing services and performance, tuition payments can run well, and can speed up data information services for parties in need, such as students, the finance department and reports to the principal.